Treatment of all types of candidiasis stomatitis in children and adults (Texas Journal of Medical Science, 2024)
Candidiasis stomatitis, commonly referred to as oral thrush, is a fungal infection caused by the overgrowth of Candida species, particularly Candida albicans. This condition affects both children and adults, with varying clinical presentations and therapeutic challenges. Effective treatment involves antifungal medications, lifestyle modifications, and addressing underlying causes. This article presents a comprehensive review of the types of candidiasis stomatitis, treatment strategies, and outcomes in pediatric and adult populations.